Penggunaan Telemonitoring Meningkatkan Kualitas Layanan Keperawatan : Tinjauan Literatur - Nadeak, Sari Eprina; Herawati, Tuti (Universitas Fort De Kock Bukittinggi, 2020)
Introduction: Telemonitoring improves quality nursing care, its make decisions quickly and accurately based on the signs and symptoms of patients who are monitored everyday. The use of telemonitoring also has the potential to increase nurse productivity, where documentation time is reduced so that nurses have more time doing patient care activities. Purpose: Provide an overview and ideas of the benefits of telemonitoring in various diseases that facilitate observation and save nurses' time in improving the quality nursing care through literature review.Discussion: Results of review from 10 selected journals, concluded that the use of telemonitoring at home and hospitals in various disease mostly feasible to apply, although in some studies there are no significant differences between telemonitoring and without telemonitoring. Recommendation: Examine the effectiveness of the use of telemonitoring in specific diseases can be done by subsequent researchers.Keywords: Telemonitoring, Quality Nursing Care, Nursing Time